(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Biorhythms (from the Greek "bios" and "rytmos" - life and coherence) are periodic changes in the intensity of physiological and mental processes over a certain period of time. Biorhythms are inherent in all living things on Earth and are a prerequisite for ensuring normal life in unison with the main rhythms of nature, caused by the rotation of the Earth around the Sun and the Stars, and the associated changes in the seasons, day and night, the influence of the phases of the Moon, sea tides, etc.Good health and a high level of human performance depend on the synchronization of the body’s vital functions, i.e. the ability of the central nervous system to ensure the interaction of various periodic functions of the body and the coincidence in time of the body’s rhythm with the rhythm of the environment.Thus, it has been established that the heart rate and breathing rhythm in a healthy person have a ratio of 4:1. Moreover, changes in this ratio indicate a disruption of certain connections in the body and allow us to draw a conclusion about possible disruptions in its functions and even about the appearance of disruptions in health.